A sequence-ready map of the human chromosome 1q telomere. - Xiang, Z; Morse, E; Hu, X; Flint, J; Chi, H; Grady, D; Moyzis, R; Riethman, H (2001)
A 260-kb half-YAC clone derived from human chromosome 1q was mapped at high resolution using cosmid subclone fingerprint analysis and was integrated with overlapping clones from the telomeric end of a separately derived 1q44 BAC contig to create a sequence-ready map extending to the molecular telomere of 1q. Analysis of 100 kb of sample sequences from across the 260-kb region encompassed by the half-YAC revealed the presence of EST sequence matches corresponding to 12 separate Unigene clusters and to 12 separate unclustered EST sequences. Low-copy subtelomeric repeats typical of many human telomere regions are present within the distal-most 30 kb of 1q. The previously isolated and radiation hybrid-mapped markers Bda84F03, 1QTEL019, and WI11861 localized at distances approximately 32, 88, and 99 kb, respectively, from the 1q terminus. This sequence-ready map permits high-resolution integration of genetic maps with the DNA sequences directly adjacent to the tip of human chromosome 1q and will enable telomeric closure of the human chromosome 1q DNA reference sequence by connecting the molecular 1q telomere to an internal BAC contig.